Performance Evaluation and Microstructure Characterization of Metakaolin-Based Geopolymer Containing Oil Palm Ash - Abideng Hawa; Danupon Tonnayopas; Woraphot Prachasaree (The Scientific World Journal)
This study reports on the microstructure, compressive strength, and drying shrinkage of metakaolin (MK) based geopolymers produced by partially replacing MK by oil palm ash (OPA). The OPA was used as raw material producing different molar ratios of SiO2/Al2O3 and CaO/SiO2. The geopolymer samples were cured at 80°C for 1, 2, or 4 hours and kept at ambient temperature until testing. The compressive strength was measured after 2, 6, and 24 hours and 7 and 28 days. The testing results revealed that the geopolymer with 5% OPA (SiO2 : Al2O3 = 2.88 : 1) gave the highest compressive strength. Scanning electron microscopy (SEM) indicated that the 5% OPA sample had a dense-compact matrix and less unreacted raw materials which contributed to the higher compressive strength. In the X-ray diffraction (XRD) patterns, the change of the crystalline phase after heat curing for 4 hours was easily detectable compared to the samples subjected to a shorter period of heat curing.